2013
DOI: 10.1371/journal.pone.0061237
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Potential Bias when Directly Comparing Standardised Mortality Ratios for In-Unit Neonatal Mortality

Abstract: IntroductionThe Standardised Mortality Ratio (SMR) is increasingly used to compare the performance of different healthcare providers. However, it has long been known that differences in the populations of the providers can cause biased results when directly comparing two SMRs. This is potentially a particular problem in neonatal medicine where units provide different levels of care.MethodsUsing data from The Neonatal Survey (TNS), babies born at 24 to 31 weeks gestational age from 2002 to 2011 and admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Variation in the values of the SMRs reduced as the size of the PICU increased, similar to the pattern seen in acute neonatal care 26. The variation was less between the largest units, partly because the large units had patient populations similar to each other but also because their case-mix was similar to the overall population: both of these factors reduce the variation in the observed SMRs.…”
Section: A More Realistic Example: Mortality In Paediatric Intensive supporting
confidence: 53%
See 2 more Smart Citations
“…Variation in the values of the SMRs reduced as the size of the PICU increased, similar to the pattern seen in acute neonatal care 26. The variation was less between the largest units, partly because the large units had patient populations similar to each other but also because their case-mix was similar to the overall population: both of these factors reduce the variation in the observed SMRs.…”
Section: A More Realistic Example: Mortality In Paediatric Intensive supporting
confidence: 53%
“…We have previously reported the potential differences in the value of SMR for neonatal units in the East Midlands and Yorkshire regions of England 26. It was shown that, when applying the risk-specific mortality of one neonatal unit to another and the ratio of their SMRs calculated, that these ratios ranged from 0.79 to 1.68: that is, the value of the SMR for one unit was 68% greater than that of another even when their risk-specific probabilities of death were identical.…”
Section: Is This Really a Problem In Practice?mentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to those of a previous study by Kim et al ( 17 ), who reported that improvements in survival rates of premature infants in Korea were dramatic during the early 1990s, and studies from the United States and Canada reporting that continued improvements in VLBWI survival rates were no longer seen after the 2000s ( 3 4 26 ). Actually, confirming the age-based survival rates according to previously published reports without collecting continuous treatment outcome data can create a significant amount of errors ( 3 13 14 27 28 29 ). Particularly in Korea, nationwide surveys on premature infant survival rates prior to the 2000s did not exist, and mostly treatment outcomes from single institutes (including four multi-center studies) of varying sizes and levels had been reported with some overlapping survey periods.…”
Section: Discussionmentioning
confidence: 96%
“…Further developing the Paradox for non-parametric settings, Haunsperger [18] discovers a computable criterion by which the consistency (upon aggregation) of an ordinal data set (when KW-tested) can be characterized. Bargagliotti [34] finds that Bhapkar's V test [35] and the Wilcoxon-Mann-Whitney (WMW) test [Wilcoxon 1945, Mann andWhitney 1947]-two other central non-parametric tests-are also not generally consistent upon aggregation. Hao and Houser [38] state, "Both robust and simple to implement, [the WMW test] has gained exceptional popularity among empirical scientists, even social scientists.…”
Section: Introductionmentioning
confidence: 99%